Pengaruh Waserda Kud Rahmad Tani (Kud Rata) Bagi Masyarakat PIR ADB - Hartanti, Sylvyana Ade; Perkasa, Rypho Delzy (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is intended to fulfill the final assignment of the Cooperative Economics course. Cooperative is a business entity or organization that is run based on cooperative principles and uses the principles of kinship and mutual cooperation to help the community economy. There are various kinds of cooperative arrangements, one of which is the Village Unit Cooperative which is intended to help rural communities, the economic activities in the Village Unit Cooperative include production, consumption, distribution, goods and service provision businesses including savings and loans, transportation, insurance, and housing. So that this research has a goal to know and analyze the organization of the Village Unit Cooperative built in the plantation area of PT Bina Rahmad Madani and find out about how the influence of Waserda for the community around the KUD Rahmad Tani environment.